PEMBENTUKAN KARAKTER ISLAMI DALAM HADIS DAN IMPLIKASINYA PADA JALUR PENDIDIKAN NON FORMAL - Yuliharti Yuliharti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Education plays a very important role in ensuring the survival of the state and nation. The rise of various types of crime, brawls between students, cases of underage children, and the use of illegal drugs, as well as corruption cases that are increasingly becoming increasingly an indication of moral decline or moral decline. Therefore, the formation of Islamic character both in the family, the school and in the community becomes a necessity and necessity and must work together and support each other. Therefore, in the current era of globalization, it is very important to look for appropriate efforts as a reference in shaping Islamic character so that it can give birth to a generation that excels in character. Modeling the pattern of the Prophet Muhammad in shaping the character of the generation of friends from the jahiliyyah character into an Islamic character is a smart and appropriate effort for now and therefore, he is known as a prophet who is also a very successful educator in the world of education. This paper aims to reveal the formation of Islamic character that has been carried out by the Prophet and its implications in the path of non-formal education.